A comprehensive review of digital marketing strategies ‎for e-commerce success - Ahmed Shaban , Awaz; Zeebaree, Subhi R. M. (International Journal of Scientific World, 2025)
The exponential advancement of digital technologies has reshaped the global e-commerce landscape, driving innovation and ‎creating both opportunities and challenges for businesses. This paper delivers an in-depth analysis of digital marketing strate-‎gies, including search engine optimization (SEO), social media engagement, content marketing, email marketing, and emerging ‎technologies like artificial intelligence (AI), blockchain, and augmented reality (AR). It highlights their transformative impact on ‎consumer engagement, operational efficiency, and competitive advantage. Furthermore, this study evaluates the integration of ‎cloud computing into digital marketing, showcasing its role in enhancing data analytics, scalability, and personalization. Case ‎studies on Amazon and Alibaba illustrate diverse strategies in different markets, offering insights into effective models for lev-‎eraging digital marketing and cloud computing. This comprehensive exploration addresses existing gaps, identifies future re-‎search directions, and provides actionable guidance for academics, practitioners, and policymakers to optimize digital market-‎ing strategies in the rapidly evolving e-commerce sector‎.